2002
DOI: 10.1038/sj.npp.1300105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixed-Action κ/μ Opioids on Cocaine Self-Administration and Cocaine Discrimination by Rhesus Monkeys

Abstract: k-Opioid agonists may functionally antagonize some behavioral effects of cocaine, but the role of mixed k/m receptor activity is unclear. The effects of three mixed k/m agonists (MCL-101, (À)cyclorphan, and Mr2034) and one k-selective agonist (enadoline) on cocaine selfadministration and cocaine discrimination were compared in rhesus monkeys. Acute treatment with all k agonists dose dependently reduced cocaine-maintained responding and produced a downward shift in the cocaine self-administration dose-effect cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 39 publications
8
77
0
1
Order By: Relevance
“…Enadoline, a selective kappa-opioid receptor agonist, also did not attenuate the effects or selfadministration of intravenous cocaine (Walsh et al, 2001). Chronic treatment with the mixed kappa-and mu-opioid receptor agonist MCL-101, however, did reduce cocaine self-administration in a non-human primate model (Bowen et al, 2003).…”
Section: Mu-and Kappa-opioid System and Addictionmentioning
confidence: 81%
“…Enadoline, a selective kappa-opioid receptor agonist, also did not attenuate the effects or selfadministration of intravenous cocaine (Walsh et al, 2001). Chronic treatment with the mixed kappa-and mu-opioid receptor agonist MCL-101, however, did reduce cocaine self-administration in a non-human primate model (Bowen et al, 2003).…”
Section: Mu-and Kappa-opioid System and Addictionmentioning
confidence: 81%
“…In preclinical studies, kappa opioids attenuated many of the abuse-related and locomotor-activating effects of cocaine, and these findings suggested that kappa opioids might be useful for the clinical treatment of cocaine abuse (Archer et al, 1996; see for a review Mello and Negus, 2000). Cocaine self-administration studies in non-human primates indicated that kappa opioids with mu receptor activity reduced cocaine selfadministration more effectively, and with fewer adverse side effects, than kappa selective opioids Bowen et al, 2003). Accordingly, we chose nalbuphine from the very limited number of kappa opioids approved for clinical use by the FDA.…”
Section: Discussionmentioning
confidence: 99%
“…Both EKC and Mr2033 appear to act as low efficacy agonists at mu opioid receptors and as high efficacy agonists at kappa opioid receptors. Subsequent studies in rhesus monkeys confirmed that mixed mu/kappa opioids were more effective in reducing cocaine selfadministration than kappa selective opioids, and produced minimal side effects (Bowen et al, 2003). Taken together, these studies suggested that mixed mu/kappa opioids may provide a useful approach to treatment of cocaine abuse.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations